On co-dependent power-law behavior across cryptocurrencies - Grobys, Klaus (Elsevier, 2024)
Using daily returns on large-cap altcoins, this paper uses power-law functions to model cryptocurrency-specific exposure to events exhibiting potentially large standard deviations. Since our analysis provides evidence for power-law behavior in the returns on cryptocurrencies, co-fractality analysis is employed to explore potential co-dependencies in the heavy-tailed part of return distributions. The findings indicate that the potential arrival of events exhibiting large standard deviations in Bitcoin returns can hardly be diversified using other sample altcoins. Other altcoins exhibit very similar features in terms of co-dependencies. Further results show that co-fractal behavior is not specific to any subsample.
Keywords: Bitcoin; Co-dependency; Co-fractality; Cryptocurrency; Diversification; Risk; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|